Language, NGOs and inclusion: the donor perspective. Issue 2 (17th February 2019) - Crack, Angela M.
ABSTRACT: Listening to communities is valued by UK's Department of International Development (DFID) for contributing to "beneficiary" empowerment and programme efficiency. This article is based on interviews with elite DFID officials to explore their understandings on how they expect NGOs to engage with local languages and the role of language intermediaries. It uncovers their perceptions of the ways that languages and cultural knowledge shape NGO relationships with communities. It finds that the officials assume that listening is unproblematic for NGOs, and ask few questions about translation and interpretation. The article concludes by reflecting on policy implications and directions for further research.